Job Grading Method Analysis As A Basis For Determining Compensation Systems In SMEs - Ilham Gustyantoro; Helmy Fauzan Wijaya; Ananda Putra Hermawan; Naufan Akbar Darmawan; Dwi Ananda Cesario (International Journal of Social Service and Research, 2021)
Most employees accept a job because of the compensation offered to them. Employees are generally motivated to put more effort into their work when they feel that their work gives them the things they value. The object of this research is SME XYZ which is engaged in the culinary industry, especially bread production with a total of 20 employees. This study uses a descriptive method with a qualitative approach to uncover compensation management in bread producers. Data collection was carried out using interview instruments. The location of this research was carried out on XYZ SME which is a bread producer in DKI Jakarta, the research was carried out from August 2021 to September 2021. The resource persons in the study were the Owner of SME XYZ and all employees of SME XYZ. Analysis of research data carried out in this study was by means of a single case analysis, starting from determining the research subject, determining data sources, data collection, data analysis, drawing data reduction, drawing conclusions and compiling research reports on compensation management in XYZ SMEs. The compensation system in SME XYZ is analyzed using job grading method based on the weight and value of the position. The results of the analysis that have been conducted state that there are 3 levels in the salary grade of UKM XYZ using the Given Grade method, whereas if using the Min Max method there are 4 levels